DAMPAK PEMBERLAKUAN ATURAN TENTANG LARANGAN HIDUP BERSAMA TERHADAP WISATAWAN ASING DI INDONESIA - Rosmahalani, Ana; Ratnawati, Elfrida (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research will also help restore in regulations and law in Indonesia, especially those regulated in Article 412 between adult men and women who live together in the sanctity of marriage. Investigating the legal consequences of Articles 411 and 412 of the Criminal Code in the tourism sector in Indonesia is the aim of this research. This analysis shows that the application of Article 412 of the Criminal Code can conflict with ethical, legal and religious principles. Law Number 1 of 2023 which states that regional regulations and national laws can interpret legal provisions so that they will have a negative impact on the business and tourism sectors in Indonesia.Keywords: Hukum Perzinahan, Hidup Bersama, Wisatawan Asing